THE MODERATING ROLE OF INVESTMENT OPPORTUNITIES BETWEEN MANAGERIAL CAPABILITY AND TAX AGGRESSIVENESS - Widuri, Retnaningtyas; Meviana, Caroline; Harianto, Vallen (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2024)
This research was conducted with two objectives, namely to test whether managerial ability can affect corporate tax aggressiveness, and to examine the role of investment opportunities as a moderating variable on the effect of managerial ability and tax aggressiveness. The sample used includes 129 manufacturing companies listed on the Indonesia Stock Exchange during the 2018-2022 period. This study used regression analysis using STATA 18. Managerial ability in this study was measured using the Data Envelopment Analysis (DEA) approach, tax aggressiveness was measured by the Book Tax Differences (BTD) approach and investment opportunities were measured by market to book and capital expenditure. The results of the study found that managerial ability had a positive effect on tax aggressiveness and investment opportunities strengthened the influence between the two. This research contributes to see how investment opportunities moderate and affect managerial ability towards tax aggressiveness. This will be useful for investors where they can view company reports and can be used to show market perceptions of the value of certain shares. There is also where this research contributes so that companies that prepare financial reports can present quality reports and avoid fraud. It also affects investors so that they can read financial reports clearly and use them to show market perceptions of the value of certain shares